Investigation of the potential effects of firefighting water additives on soil invertebrates and terrestrial plants. (February 2023) - Anderson, J.; Prosser, R.S.
Abstract: The intensity and frequency of forest fires is increasing across the globe due to climate change. Additives are often added to make water more effective at extinguishing fire and preventing re-ignition. This study investigated the toxicity of nine different firefighting water additives to four species of soil invertebrates ( Folsomia candida, Porcellio laevis, Porcellio scaber, and Trichorhina tomentosa ) and two plant species ( Agropyron cristatum and Raphanus sativus) . Considerable variation in toxicity was observed among the firefighting products. The toxicity of individual products also varied considerably amongst the tested species. A hazard assessment was conducted by comparing the concentration of firefighting water additive that caused a 50% effect (LC50 or EC50) or a concentration that caused no effect (NOEC) to the concentration recommended by the manufacturer. At a rate of application representative of a forest firefighting scenario, most firefighting water additives tested in this study posed a hazard to F. candida and the three isopod species. The majority of products did not pose a risk to the two plant species included in this study. Consideration of the toxicity of firefighting water additives to terrestrial biota should be considered along with the efficacy of the product to fight fires when deciding which products to use. Graphical abstract: Image 1 Highlights: Forest fire frequency and severity is increasing with climate change. Investigated toxicity of 9 firefighting water additives to 6 soil species. Toxicity between species tested varied by one order of magnitude. Majority of water additives posed a hazard to soil invertebrates. Only a single water additive posed a hazard to plants.